Hábitos de Lectura en el desarrollo de una escritura creativa de los niños y niñas del séptimo año de Educación General Básica, de la Unidad Educativa Fiscal Numa Pompilio Llona de la parroquia Itchimbia, cantón Quito, provincia de Pichincha, durante el año lectivo 2019- 2020 - Piedra Barros, Katya Mabel (2020)
Ecuadorian education has undergone major changes in recent times with the aim of improving educational quality, in what has to do with children's reading and writing, fundamental for the entire process of education at all levels, Hence, when observing the deficiency in reading, it is necessary to carry out this educational and important intervention. For the intervention the authorization of the director of the educational unit was obtained, the diagnosis was made, applying the survey with eleven questions, five questions for each variable and one for the proposed intervention and the observation sheet to record what was observed in the classroom, a sample was taken (twenty-three girls and sixteen boys) with the obtained results allowed to formulate the intervention problem: scarce reading habits in seventh-year students of basic general education, the research was bibliographic, documentary In the field of an exploratory and descriptive type, the appropriate documentation that I provide to solve the problem was compiled, a brief introduction and the expected objectives are presented. As a general objective, promote reading habits in the development of creative writing in boys and girls of seventh year of basic general education, from the Fiscal Education Unit "Numa Pompilio Llona" of the Itchimbia parish, Quito canton, Pichincha province, during the 2019-2020 school year. The development of the proposal is presented with a brief introduction on the development of a guide to strategies to promote reading habits, the same that contains thirty-eight application teaching strategies to promote reading habits in students and develop creative writing. These strategies were applied to thirty-nine students who correspond to the intervened sample of seventh-year students in basic education. At the end of each strategy, an image can be seen as evidence of the strategy developed, and then the general evaluation below shows the obtained results, conclusions of the intervention proposal, bibliographic references and general annexes are cited respectively